PENINGKATAN HASIL BELAJAR SISWA PADA PEMBAGIAN MENGGUNAKAN MEDIA PERMAINAN ARCADEMICS DI KELAS IV B SD NEGERI SUNGGUMINASA V - Fitriani Fitriani; Indah Marjan Utami; Sakmariana; Randi Saputra Mahmud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem in this research is how to use arcademics game media to be able to describe the increase in learning outcomes for class IV B students at SD Negeri Sungguminasa V. This research aims to describe the increase in student learning outcomes in divisions using arcademics game media for class IV B students at SD Negeri Sungguminasa V This type of research is classroom action research (Class Action Research) which consists of two cycles where each cycle is carried out in two meetings. Research procedures include planning, implementing actions, observing and reflecting. The subjects in this research were 22 students in class IV B at SD Negeri Sugguminasa V. The results of the research show that: a) cycle I student activities obtained the value obtained from the student evaluation results increased from the value of the pre-test results. A total of 7 students obtained scores with very good criteria, 7 students with fairly good criteria and 8 students with poor criteria. In cycle II there were 10 students who obtained very good criteria scores and 12 students with fairly good criteria. b) increasing learning outcomes in the division of students in cycle I with 22 students or all students, the average percentage of completeness achieved was 63.6% with 14 students having achieved completeness and 8 other students not yet. In cycle II the average percentage of completeness achieved was 100% with 22 students or all students achieving completeness. Based on the results of the research above, it can be concluded that using arcademics game media is able to improve learning outcomes for class IV B students at SDN Sungguminasa V.